On the problem of development of a human-based social ontology - Donnikova, Iryna (Actual Problems of Mind, 2017)
The paper deals with understanding humanity in the context of a new ontology as a self-organized social being. The author claims that such an ontology should be based on the principle of co-evolution of the nature, mankind and society which should promote an xplication of the ways of social self-organization.